Increase in carbon monoxide observed by satellites in the Northern Hemisphere over the summers of 2008-2023, linked to an increase in wildfires - Ehret, Antoine; Turquety, Solène; George, Maya; Hadji-Lazaro, Juliette; Clerbaux, Cathy (Atmospheric chemistry and physics, 2025)
Biomass burning has a significant impact on the composition of the atmosphere and climate due to large emissions of trace gases and aerosols. Previous studies have demonstrated the influence of biomass burning emissions on the spatial and temporal variability of carbon monoxide (CO) and aerosol concentration on hemispheric scales. This study aims to examine the variability of fires and their impact on the mean and extreme values of CO and aerosol optical depth (AOD) observed by satellites (IASI/Metop for total column CO and MODIS/Terra and Aqua for AOD), focusing on the extratropical Northern Hemisphere (NH) from 2008 to 2023. While biomass burning due to agricultural practices is decreasing in many regions, boreal regions and the western United States have experienced a notable rise in burned area, up to +37 % in recent years (2017-2023) compared to the 2008-2023 period, and fire intensity. This is consistent with an increase in meteorological fire risk in these regions. The increase in wildfires has led to a rise in the mean and extreme values of CO and AOD during the summer and early autumn across the whole of the NH, up to +9.3 % and +33 % for extreme values of total column CO and AOD in boreal regions and the western United States in recent years compared to 2008-2023. The number of days with extreme total column CO and AOD has increased by more than 50 % in recent years during summer in North America, the Atlantic and Europe, in comparison to the full period. A robust correlation (r = 0.83) between the number of plumes and burned areas in the extratropical Northern Hemisphere is obtained.